Rotavirus specific maternal antibodies and immune response to RV3-BB rotavirus vaccine in central java and yogyakarta, Indonesia. Issue 16 (3rd April 2020) - Danchin, Margie H.; Bines, Julie E.; Watts, Emma; Cowley, Daniel; Pavlic, Daniel; Lee, Katherine J.; Huque, Hamidul; Kirkwood, Carl; Nirwati, Hera; At thobari, Jarir; Dewi Satria, Cahya; Soenarto, Yati; et al.
Highlights: IgA in breast milk was not associated with reduced RV3-BB vaccine take in Indonesia. IgG titre in cord blood was associated with lower vaccine immunogenicity after one, not three doses of vaccine. RV3-BB vaccine appears to be able to be given with breast-feeding in high rotavirus disease burden settings. Abstract: Background: Placental or breast milk maternal antibodies can potentially reduce oral rotavirus vaccine efficacy in developing countries. We aimed to examine the relationship between the level of rotavirus specific immunoglobulin A (IgA) and neutralising antibodies (NA) in colostrum and breast milk and cord IgG, with cumulative vaccine take following one and three doses of oral RV3-BB rotavirus vaccine within a Phase IIb trial in Indonesia. Methods: 196 infants received three doses of RV3-BB in a randomized, double-blinded trial, using a neonatal schedule (first dose at 0–5 days of age, n = 61), an infant schedule (first dose at ~ 8 weeks of age, n = 67) or placebo (n = 68). Rotavirus specific IgA and NA in colostrum and breast milk, rotavirus specific cord IgG, Serum IgA and stool excretion were measured. Results: There was little evidence of an association between IgA in colostrum or breast milk and cumulative vaccine take after three doses in the neonatal or infant groups. In the neonatal group, there was a negative association between IgG titre in cord blood and cumulative vaccine take (odds ratio [OR] 0.96; 95% confidence interval [CI] 0.92–1.00; p = 0.03) and serum IgA response (OR 0.94; 95%CI 0.89–0.99; p = 0.02) after one dose of vaccine, which were not evident after three doses in the neonatal or infant groups. Conclusions: Amongst Indonesian infants we did not find an association between IgA in colostrum or breast milk and vaccine take after 3 doses of RV3-BB vaccine. Maternal rotavirus antibodies in breast milk appear to have minimal impact on RV3-BB vaccine take when administered with a short delay in breast-feeding in settings with a high rotavirus disease burden.